Active ageing and solidarity between generations in Europe. First results from SHARE after the economic crisis - Weber, Guglielmo (De Gruyter, 2013)
SHARE is an international survey designed to answer the societal challenges that face us due to rapid population ageing. How do Europeans age? Under which circumstances do older people and their families live, how healthy and active are they, and how did the crisis affect them? The authors of this multidisciplinary book have taken a first step toward answering these questions based on the recent SHARE data including a new social networks module.